CONCEPTUAL RESEARCH ON THE TERM FACILITATION: REDUCING AN ELEPHANT TO CHEWABLE CHUNKS - Schenck, Rinie; Louw, Huma (Social Work/Maatskaplike Werk, 2008)
The term “facilitation” is often used in promoting social change and used by change agents to refer to many actions they perform to bring about learning, change and development. For instance, in training and education the terms used are “facilitators” and “learners” and in other contexts facilitation is more comprehensive than merely facilitating learning. It may include different types of change and development. Soal (2004:55) refers to the latter form of facilitation as “facilitation through the change threshold”. Often change agents refer to their actions as facilitation, but do not clearly describe the meaning of the concept, or they act in such a way that it cannot be regarded as facilitation but rather as instruction, induction or top-down methods. The need for this article arose because of this lack of clarity and the different meanings that are attached to the concept of facilitation and its theoretical base.